Fermentation quality and bacterial ecology of red clover dominated silage modulated by different management factors - Franco, Marcia; Tapio, Ilma; Huuskonen, Arto; Rinne, Marketta (Frontiers in Animal Science, 2022)
Identification of bacterial communities in both the raw material and the subsequent silages provides new insights into understanding the silage fermentation process. The objective was to evaluate how different silage management factors affect silage preservation characteristics, the microbiome, and their correlations. A red clover dominated sward was used as the raw material and ensiled in pilot scale using a 3 × 4 design, with three management conditions including the level of compaction (loose and tight), and further, for the tightly compacted silages contamination with soil and faeces was conducted; and four different additive treatments with different modes of action: Control without additive (CONT), formic and propionic acid-based additive (FPA), homofermentative lactic acid bacteria inoculant (LAB) and salt-based additive (SALT). Samples of the raw material and subsequent silages were taken and routinely analysed, including DNA extraction and PCR amplification using universal primers. Tight compaction reduced slightly the extent of silage fermentation, but contamination with soil and faeces stimulated a non-desired type of fermentation with higher concentrations of ethanol, acetic acid and propionic acid and a higher pH. Use of LAB and SALT had only minimal effects on silage fermentation, but FPA clearly restricted fermentation and resulted in a better fermentation quality (lower pH, ammonia N and acetic acid concentration) of the silages compared to CONT. The FPA silages presented greater diversity of bacterial communities compared to the other silages. Proteobacteria were the most abundant in raw material, followed by Firmicutes, and major shifts happened in these communities during the silage fermentation process. Weissella was found in small amounts in the raw material but it dominated in the silages. The most abundant communities in the silages, such as Weissella, Lactobacillus and Pseudomonas, were correlated with several silage fermentation characteristics. Use of FPA improved fermentation quality of silages, but SALT and LAB differed from CONT to a smaller extent. All additives modified the bacterial profiles of grasses ensiled under different management conditions. The combination of parameters related to silage quality and bacterial communities provided a deeper understanding of the silage fermentation process and how they can be manipulated to obtain better feed quality.